Penguatan Kapasitas Digital Pemerintah Desa Tanjung Baru Ranau melalui Sosialisasi Literasi dan Penyediaan Infrastruktur Teknologi - Sena Putra Prabujaya; Perdana, Dimes Akbar; Novitry Pratiwi; Galuh Efnol Adzan; Elfandari (LOSARI DIGITAL, 2026)
The development of digital technology requires village governments to have adequate digital literacy skills to improve the quality of public services and encourage the realization of smart villages. However, limited literacy among village government officials and the lack of technological infrastructure in the form of stable internet network access pose challenges in Tanjung Baru Ranau Village. This Community Service activity aims to strengthen the digital capacity of village government officials through digital literacy socialization and the provision of technological infrastructure. The implementation method includes socialization, provision and assistance with the installation of technological infrastructure, and evaluation. The results of the activity showed an increase of 158.62% in the average score from 5.8 in the pre-test to 15 in the post-test in the knowledge and skills of village officials related to internet use, as well as the use of technology in public services. The provision of technological infrastructure also strengthens access and readiness of village infrastructure to support digital transformation and is a strategic step towards the implementation of digital-based governance and smart village development.